Synthesis of C2 Hybrid Amide‐Based PTC Catalysts and Their Comparison with Saturated Analogues. Issue 21 (4th June 2020) - Majdecki, Maciej; Niedbala, Patryk; Jurczak, Janusz
Abstract: We investigated the synthesis and catalytic efficiency of four new C2 hybrid PTC catalysts and their saturated analogues with reduced double bond. These eight novel hybrid catalysts can be straightforwardly synthesized with good yields and high structural design diversity (with various linkers). The catalytic efficiency of our catalysts was systematically investigated using a glycine imine alkylation reaction, carried out under PTC conditions. It was found that saturated catalysts show both higher reaction yield (up to 98%) and enantioselectivity (up to 94% ee ). Abstract : A novel family of Cinchona alkaloid C2 catalysts containing diamide linkers was designed. These hybrid derivatives were used in the asymmetric alkylation of glycine imine ester. Catalytic efficiency of the amide derivatives depends on the substituent in the phenyl ring. The corresponding alkylated products were obtained with excellent yields (up to 98%) and very high enantioselectivities (up to 94% ee ) using various benzyl bromides. It was found that saturated catalysts exhibit higher selectivity in examined reaction.